Political system : an inquiry into the state of political science - Easton, David (New York, 1965)
ERIOUS STUDENTS OF POLITICS shonld fnd this book stimulating and ul for its reflective view of the state American political science today. he argument of the book, briefly stated, is that political scientists could better explain our political life if they had paid closer attention to general or systematic theory. No attempt is made here to pre- Sent a general theory. Instead, the author discusses some of the problems that confront political scientists if they are to develop a systematic science. He considers broad concepts by virtue of which the subject matter of political science can be identified and organzed. He examines the kinds of data essential to a proper description of any political event. And he analyzes the relation of moral judgments to the study of political theory. No other book provides so lucid an analysis of the types of political thought, their functions, and their interelations. Students of political scifence will find it indispensable for its persuasive exposition of the nature and scope of their subject. It sharply out- lines the tasks challenging a new genration of political scientists.
Keywords: Political Science